Optimal power interface topology for DC grid connected LED lighting system - Tan, Y. K. (2013)
Lighting represents an important area of research owing to its status of being one of the largest consumers of electricity in buildings. With increasing emphasis on the realization of net zero energy buildings (NZEB) to achieve energy conservation, more attention is being devoted to the design of high efficiency lighting systems. LED lighting has been enjoying higher favor because of significant advantages that it has over traditional lighting sources such as incandescent lamps, CFLs and so on. Due to the DC nature of the LED lights, it makes greater sense to employ a low voltage DC (LVDC) grid to power the system instead of a traditional AC one. This eliminates additional power converter stages, leading to greater efficiency. This paper aims to explore the feasibility of such an LVDC powered system with a single-stage universal driver to power LED lighting loads.